Analog of the Krein Formula for Resolvents of Normal Extensions of a Prenormal Operator - Dudkin, M. Ye. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove a formula that relates resolvents of normal operators that are extensions of a certain prenormal operator. This formula is an analog of the Krein formula for resolvents of self-adjoint extensions of a symmetric operator. We describe properties of the defect subspaces of a prenormal operator.